The normal spectral emission characteristics of Ni-based alloys during oxidation at high temperatures. (January 2019) - Zhao, Shunan; Li, Xunfeng; Huai, Xiulan; Zhou, Xiaoming; Cheng, Keyong
Highlights: Emissivity of Ni-based alloys at high temperatures is estimated during oxidation. Emissivity oscillations occur due to interference from the oxidation film. The emissivity increases as temperature increases and wavelength decreases. Fitting models are developed to study the change of the emissivity quantitatively. Abstract: The emissivity change due to oxidation of the Ni-based alloys that are used for turbine blades in severe environment will cause large errors in radiation thermometry. In this paper, the normal spectral emissivity of three Ni-based alloys DZ125, DD6 and K465 is experimentally measured during oxidation at about 810, 914 and 998 °C in air. And the measurement wavelength varies from 1.35 to 2.35 μm. The combined standard uncertainties of the normal spectral emissivity are less than 3%. The oscillations of the emissivity are observed, and the effects of oxidation temperature, heating time and wavelength on the emissivity are investigated. The oscillations of the emissivity are produced with growth of the oxidation film by the interference effect between the direct transmission radiation and the transmission radiation after reflections by the substrate and air/film interface emitted by of the substrate. The oscillation extremums of the emissivity shift towards larger wavelengths as the oxidation process proceeds. The results show that the normal spectral emissivity increases basically with increasing temperature and decreasing wavelength except for the occurrence of the oscillations of the emissivity. The normal spectral emissivity increases rapidly at the initial heating time, and the change of emissivity becomes slow when the oxidation tends to be saturated gradually. Furthermore, the emissivity models versus heating time and wavelength are established, which fit the experimental results very well. The relative errors of the fitting models for emissivity are less than 4%.